Pedagogical Translanguaging by EFL Teachers in English Classes in Vietnam - Van, Nguyen Pham Thanh; Huong, Le Pham Hoai; Ha, Huynh Thi Long (Masyarakat Linguistik Indonesia Universitas Andalas, 2025)
This study was undertaken to explore the ways EFL teachers used translanguaging between English and Vietnamese in their classes at a university context. Specifically, it aimed to document the alignment of translanguaging theory with classroom evidence in response to calls for research in this direction. A mixed methods design was adopted to conduct the study. Data were collected from two sources: recorded classroom observations in the natural EFL classes in Vietnam and stimulated recall interviews. The stimulated recall interviews with EFL teachers were carried out when the recording had been completed and extracts of the teachers’ translanguaging reviewed. The extracts indicate that during their English teaching, the EFL teachers employed translanguaging frequently to manage classroom activities, provide emotional support, and encourage students’ participation. Besides, the stimulated recall interviews reveal that the teachers translanguaged purposefully to scaffold students with English vocabulary and grammar. They also switched between the two languages to create humor and foster a friendly classroom environment to make students feel comfortable during learning. Their use of translanguaging was found to facilitate students’ metalinguistic awareness and learning new concepts in the English lessons. Overall, the findings from both sources complement each other, revealing the purposeful translanguaging of the teachers for both teaching and managing classes. The study’s findings contribute to supporting intentional translanguaging in context-sensitive language instruction. In addition, the results provide practical implications for EFL teachers to employ translanguaging to assist students in their English learning and more importantly to teach more effectively. The findings also suggest implications for policies embracing the use of L1 intentionally when needed by both EFL teachers and students.